Comparison of dual isolated converters with flyback converters for bidirectional energy transfer - Mapari, Rahul G.; Bhangale, Kishor; Kadlag, Sunil Somnath; Shriwastava, Rakesh (Institute of Advanced Engineering and Science, 2025)
This article demonstrates a proposed technique for improving single-stage rectifiers' power factor (PF) and controlling the load voltage in response to grid voltage and load changes. To alleviate the above problem, this article offers a novel bi-directional continuous switching pulse width modulation (CSPWM) and sinusoidal pulse width modulation (SPWM) based converter that can improve PF and reduce harmonics. This converter is evaluated based on two cases, Case I: CSPWM-based rectification and SPWM-based inversion scheme, and Case II: Rectification and inversion, both operations using the SPWM scheme. The proposed control scheme uses two Bi-directional IGBTs and two diodes, which are bridgeless, do not need a transformer, and are free from the output current sensor. The suggested scheme is simulated using MATLAB/Simulink and implemented on DSPic33FJ64mc802 platforms to validate the effectiveness of the proposed approach using two cases for a 1 KW system. The suggested control scheme provides improved PF, good voltage regulation, and depreciation in harmonics and total harmonic distortions (THD) compared to existing systems that enhance converter performance.